The Effect of The Student Team Achivment Division Type Cooperative Learning Model on Basic School Student Learning Outcomes: Pengaruh Model Pembelajaran Kooperatif Tipe Student Team Achivment Division Terhadap Hasil Belajar Siswa Sekolah Dasar - Adawiyah, Robi’atul; Taufiq, Mohammad; Hartatik, Sri; Akhawani (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to analyze the application of the cooperative learning model of the Student Team Achivment Division type in improving the learning outcomes of elementary school students and to find out the difference in the increase in learning outcomes obtained by students when using the Cooperative learning model of the Student Team Achivment Division type. The difference in the improvement of learning outcomes obtained from 10 relevant journals was caused by the subjects selected by different researchers such as different research sites, different abilities possessed by each selected subject, and different years of research. This type of research is quantitative research using the meta-analysis method. The research begins with formulating research, looking for relevant journals available in electronic media. Based on the analysis of the cooperative learning model, the Student Team Achivment Division type can improve student learning outcomes by an average of 78.59 from the previous 53.53. Based on this research, the application of the cooperative learning model type Student Team Achivment Division can be used as a suggestion to be applied in elementary schools.